Transmission of SARS-CoV-2 in Different Districts of a County in Istanbul, March to September 2020 - TOPUZOĞLU, AHMET; BİLGİN, HÜSEYİN; KORTEN, VOLKAN (SAGE PUBLICATIONS INC, 2021)
Epidemics caused by airborne viruses in cities with large populations create a big problem as in the current COVID-19 pandemic. Cramped lifestyle, busy workplaces, crowded public transportation, and higher household member counts are responsible for the transmission of the disease. In Turkey, Istanbul has taken the lead in the number of cases since the beginning of the epidemic. The excess population density is the major cause for disease transmission. It is essential to monitor the contaminated regions with geographical information systems on city maps. Outbreak maps visualize and help analyze the patterns of transmission and serve as a communication and education tool. A dynamic heat map video of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) polymerase chain reaction positive cases in a county of Istanbul was generated. The heat map visualizes how the epidemic spread to all the districts and the cumulative cases increased in one county of Istanbul with real attack rates.
Keywords: COVID-19; heat map; communicable diseases; epidemiology; SARS-CoV-2; transmission; outbreak; CHARACTERIZE; GROWTH